Pelaksanaan Akad Fotografi Ditinjau Dari Fiqh Muamalah - Nurmayanti & Syafri Gunawan & Ahmatnijar (Jurnal El-Thawalib, 2020)
Photographing an object in Sutan Foto Studio has become a habit in certain occasions such as wedding receptions, birthdays, inaugurations, and others. Customers who want to use the services of a photographer must first register with the photographer when and where they want to go. Then the photographer will be rewarded for his work after completing his work and not being rewarded. It turned out that many customers broke their promises and the photographer felt aggrieved because they did not get anything in return even though they had done the job. From these problems, the author wants to know how to implement a photography contract at the Sutan Photo Studio, Aek Galoga Village, Panyabungan District, Mandaliing Natal District and How a Muamalah Fiqh Review of a photography contract at the Sutan Photo Studio, Aek Galoga Village, Panyabungan District, Mandailing Natal Regency. The type of research used in this research is field research, namely the author will go directly to the field to research a problem, the data used are primary and secondary data, the data collection method uses direct interview method. The results of this research are the contract in the Sutan Foto Studio, Aek Galoga Village, Panyabungan District, Mandiling Natal Regency, which is from the harmony and the conditions have been fulfilled, and in its implementation there are still mistakes or broken promises, someone (cient) has agreed with the photographer but, finally this person (client) broke his promise. According to Fiqh Muamalah, it is included in the Ingkar promise, but if seen from the terms and conditions this contract is a valid contract because both parties agree on this, only one party reneges on its promise.